Late Onset Acquired Prothrombin Complex Deficiency (APCD) in a 27 Days Old Infant: a Rare Case Report - Farahdina Farahdina; Ima Sri Wahyuni (Green Publisher Indonesia, 2021)
Acquired prothrombin complex deficiency (APCD) is a disease that occurs due to a deficiency in the coagulation factors that make up the prothrombin complex (II, VII, IX, and X), which are highly dependent on the presence of vitamin K in carrying out their functions. This study uses a qualitative method with the type of case report. The sampling technique used in this study the author uses the Random Sampling technique or by using the Slovin formula in Husein Umar. Where each population has the same opportunity to be selected as a sample in this study. Based on the analysis and discussion, it can be concluded that APCD is a disease with a high mortality rate, and those who survive are also threatened with disability for the rest of their lives. So that early detection and holistic treatment need to be done to prevent death and disability.